2013
DOI: 10.1001/jamasurg.2013.2136
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk-Adjusted Nomogram for Rectal Cancer Surgery Outcomes

Abstract: Context Circumferential resection margin is the primary determinant of local recurrence and a major factor in survival in rectal cancer. Neither chemotherapy nor chemoradiation compensates for a positive margin. Objective To identify treatment-related factors associated with hospital margin-positive resection and to develop a tool that could be used by individual hospitals to assess their outcomes based on their unique mix of patient and tumor characteristics. Design Retrospective review of the National Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…16 Also, a recent large-scale database study with 85,190 patients with rectal cancer found a small but significantly increased risk of CRM+ in men. 17 This possibly increased risk in men could be due to the anatomy of the male pelvis. After univariate analysis in the present study, N-stage was associated with increased risk of CRM+, but after controlling for other risk factors by multivariate analysis, N-stage was no longer a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…16 Also, a recent large-scale database study with 85,190 patients with rectal cancer found a small but significantly increased risk of CRM+ in men. 17 This possibly increased risk in men could be due to the anatomy of the male pelvis. After univariate analysis in the present study, N-stage was associated with increased risk of CRM+, but after controlling for other risk factors by multivariate analysis, N-stage was no longer a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Expected surgical margin-positivity cases were predicted based on patient demographic and clinical characteristics in each facility using multivariate logistic regression models. Using previously-specified methodology [18,19], we determined the significance of the O/E ratio by binominal function and used this to define facility performance status (details in supplemental methodology, supplemental Table 1). Facilities were categorized as outperforming (O/E ratio<1, p<0.05), non-outlier (p>=0.05), and underperforming (O/E ratio>1, p<0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor size was categorized into 3 groups: <1cm, between 1 and 2cm, and greater than 2cm in concordance with prior papers published on rectal cancer margin status NCDB. 22,23 The NCDB defines type of rectal surgery as a partial or total proctectomy. A partial proctectomy includes but is not limited to an anterior resection, Hartmann’s operation, low anterior resection (LAR), or trans sacral rectosigmoidectomy whereas total proctectomy includes abdominoperineal resections (APR), pelvic exenteration, and total proctocolectomy, NOS.…”
Section: Methodsmentioning
confidence: 99%